Evaluation of the Prevalence of Maxillary Sinuses Abnormalities through Spiral Computed Tomography (CT) - João Paulo Nunes Drumond; Bruna Bianca Allegro; Neil Ferreira Novo; Sérgio Luís de Miranda; Wilson Roberto Sendyk (International Archives of Otorhinolaryngology, 2017)
Abstract